ENSURING THE RIGHTS OF VICTIMS DURING THE INVESTIGATION OF WAR CRIMES (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the issues of ensuring the rights of victims during the investigation of war crimes. The authors emphasize the need to introduce the principles of the "victim-oriented" approach in the investigation of war criminal offenses in Ukraine. The victim-oriented approach in criminal proceedings means that the justice system pays special attention to the needs and interests of victims of crime. This approach puts the victim at the center of attention and is not limited to punishing perpetrators. Thus, the victim-oriented approach aims to create a fairer and more human environment in criminal justice, where attention is not limited to the rights of the accused, but also pays attention to the needs and rights of victims of crime. The main aspects of this approach in criminal justice include: providing victims with information about the status of the case, investigation and trial and their active involvement in criminal proceedings; providing comprehensive support (psychological, social, etc.) to victims and taking measures for their direct protection; providing opportunities for compensation for material and moral damage caused to the victim as a result of the crime; creating opportunities for victims to participate in decision-making related to the case, such as plea bargaining or sentencing; ensuring that criminals are punished fairly, taking into account the need to restore the rights of the victim of a crime.
Keywords: war crimes; pre-trial investigation; protection of victims' rights; victim-oriented approach